From Tap to Table: How Ease of Use, Trust, and Convenience Drive Customer Loyalty on Foodpanda - Daisy Mui Hung Kee; Si rou Tan; Man Hong Tan; Si Xian Tan; Chea Zen Tang (AIBPM Publisher, 2026)
Foodpanda, a leading food delivery platform in Malaysia, offers customers a fast and convenient way to order meals from local restaurants. Despite ranking second overall among food delivery services behind GrabFood, it holds the top position in the “Food Drink” category on the Google Play Store in terms of app downloads. This study investigates the factors influencing customer satisfaction and loyalty toward Foodpanda. Specifically, it examines the effects of perceived usefulness, perceived ease of use, perceived trust, perceived risk, and perceived convenience on customer satisfaction, as well as their impact on customer loyalty, including the role of satisfaction as a predictor of loyalty. Data was collected from 200 Foodpanda users and analyzed. Our findings indicate that perceived trust and perceived convenience significantly and positively affect customer satisfaction, while perceived usefulness, perceived trust, perceived risk, perceived convenience, and customer satisfaction significantly predict customer loyalty. Among these, perceived convenience had the strongest effect on both satisfaction and loyalty. Our findings highlight the key roles of convenience, trust, and satisfaction in shaping customer behavior in the food delivery industry.